'Counterfeit Egyptians': The construction and implementation of a criminal identity in early modern England. Issue 2 (November 2016) - Morgan, John
Abstract : English law first began to mark out 'Egyptians' as a separate, criminalised group in the sixteenth century. This article examines how statute law constructed and implemented an Egyptian identity, and the effect this had on those prosecuted. A close reading of the four Tudor Egyptian statutes is provided, and relevant material from sixteenth- and seventeenth-century legal and judicial sources is compared to assess the implementation of the statutes. By focussing on the legal construction of the Egyptian identity, this article illuminates the ways in which the early modern state attempted to exert control over 'Egyptians'. This was attempted through the application of loose definitions based around itinerancy and non-nativity that could be applied with great discretion. This 'discretionary impulse' connected the experience of 'Egyptians' with other travellers in the period, whilst enabling the agents of the State to exercise particularly close punishment and control. By examining a legally constructed identity, this article attempts to avoid reifying biases found in the traditional sources for Gypsy history in the period, and sheds light on the history of state-driven marginalisation and persecution.